Free enterprise and state control: Annual bulletin of the advisory board of the Foundation for Family Businesses - Clemens Fuest; Udo Di Fabio; Gabriel Felbermayr (Foundation for Family Businesses, 2022)
The authors Clemens Fuest, Udo di Fabio and Gabriel Felbermayr examined the efficiency of state intervention using various examples in order to analyse whether the same goals could not be achieved better and at lower cost though other instruments. Their conclusion: not everything well intended is also well done. Close control of companies leads to excessive demands.
Keywords: 330